Approximation of the deuteron wave functions and polarizing characteristics for Reid93 potential - Zhaba, V.I. (Вопросы атомной науки и техники, 2016)
Numerical coefficients of analytical forms for deuteron wave function in configuration representation for Reid93
potential are designed. The obtained wave functions do not contain superfluous knots. The designed parameters of a
deuteron well agree with the experimental and theoretical data. The polarization performances Т20 and Ауу designed
on wave functions are proportionate with earlier published. Численно рассчитаны коэффициенты аналитической формы для волновой функции дейтрона в координатном представлении для потенциала Reid93. Полученные волновые функции не содержат лишних узлов.
Рассчитанные параметры дейтрона хорошо согласуются с экспериментальными и теоретическими данными.
Рассчитанные по волновым функциям поляризационные характеристики Т20 и Ауу соразмерны с раньше
опубликованными. Чисельно розраховані коефіцієнти аналітичної форми для хвильової функції дейтрона в координатному
представленні для потенціалу Reid93. Отримані хвильові функції не містять надлишкових вузлів. Розраховані параметри дейтрона добре узгоджуються з експериментальними і теоретичними даними. Розраховані за
хвильовими функціями поляризаційні характеристики Т20 і Ауу співрозмірні з раніше опублікованими.